Architectural Felicitology - Rappaport, Alexander (project baikal, 2015)
The article features the meaning of the category “happiness” applied in the architectural theory. The author suggests a connection between a new explication of “happiness” in architecture and the categories “own place”, “close human relations” and “personal business” as well as the concepts of “the world”.
Keywords: architecture; felicitology; beauty; theory of architecture; love; taste.